2010
DOI: 10.1111/j.2041-1014.2010.00567.x
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Aggregatibacter actinomycetemcomitans serotypes in subgingival plaque from United States subjects

Abstract: This study examined the distribution pattern of Aggregatibacter actinomycetemcomitans serotypes in the subgingival plaque of subjects residing in the United States. A. actinomycetemcomitans was identified in 256 subgingival plaque samples from 161 subjects. For 190 of the 256 samples, the total cultivable bacteria and selected periodontal pathogenic species were determined. A. actinomycetemcomitans isolates were confirmed by a16S rDNA-based PCR analysis, genotyped by arbitrarily-primed PCR, and serotyped by PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
62
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 26 publications
(54 reference statements)
8
62
2
Order By: Relevance
“…As showed by several authors [9,10,17,18] the distribution pattern of A. actinomycetemcomitans serotypes varies greatly depending on the periodontal status of the allocated population and the country where the study takes place. Up to now, in Brazil, as well as in Latin America, no study had recruited a considerable number of subjects showing plaque samples positive for A. actinomycetemcomitans, and a diversity of periodontal conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As showed by several authors [9,10,17,18] the distribution pattern of A. actinomycetemcomitans serotypes varies greatly depending on the periodontal status of the allocated population and the country where the study takes place. Up to now, in Brazil, as well as in Latin America, no study had recruited a considerable number of subjects showing plaque samples positive for A. actinomycetemcomitans, and a diversity of periodontal conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, researchers don't seem to have observed a similar serotype-disease pattern. Recently, Chen et al [9] examined the distribution pattern of A. actinomycetemcomitans serotypes in the subgingival plaque of subjects residing in the United States and demonstrated that serotype c is the dominant serotype in this population. The authors also observed that serotype a was more frequently detected than serotypes b, d, e, and f. Non-typeable strains were either not detected or were relatively infrequent in the examined population.…”
Section: Introductionmentioning
confidence: 99%
“…73,74 These findings are supported by the negative association in subgingival samples between the presence of A. actinomycetemcomitans and P. gingivalis. 75 This indicates an important pre-clinical role of A. actinomycetemcomitans in AgP. However, it seems reasonable to assume that the role of this bacterium is limited in competition with the obligate anaerobic periodontal pathogens in the ecological niche of a periodontal crevice.…”
Section: A Actinomycetemcomitans In the Complex Biofilm Of The Periomentioning
confidence: 99%
“…Recently, a study conducted in the United States in 2010 observed all serotypes in the oral cavities of the participants, in varying distributions [36]. Serotype 'c' was the dominant serotype, followed by 'a' and 'b'.…”
Section: B Aggregatibacter Actinomycetemcomitansmentioning
confidence: 99%
“…Serotypes 'd' and 'e' were rare, while the prevalence of 'f' is still under investigation [37]. Additionally, patients may harbor just one serotype, or several [36].…”
Section: B Aggregatibacter Actinomycetemcomitansmentioning
confidence: 99%